PTH-104 Tumour doubling time of colorectal metastases in patients selected for liver resection does not influence post-operative disease-free survival. (22nd June 2015) - Wiggans, M; Shahtahmassebi, G; Aroori, S; Bowles, M; Briggs, C; Stell, D
Abstract : Introduction: The aim of this study was to assess the potential association between the change in diameter of colorectal liver metastases between pre-operative imaging and liver resection and disease-free survival in patients who do not receive pre-operative liver-directed chemotherapy. Method: Analysis of a prospectively maintained database of patients undergoing liver resection for colorectal liver metastases between 2005 and 2012 was undertaken. Change in tumour size was assessed by comparing the maximum tumour diameter at radiological diagnosis determined by imaging and the maximum tumour diameter measured at examination of the resected specimen in 157 patients. Results: The median interval from first scan to surgery was 99 days and the median increase in tumour diameter in this interval was 38%, equivalent to a tumour doubling time (DT) of 47 days. Tumour DT prior to liver resection was longer in patients with T1 primary tumours (119 days) than T2–4 tumours (44 days) and shorter in patients undergoing repeat surgery for intra-hepatic recurrence (33 days) than before primary resection (49 days). The median disease-free survival of the quartile of patients with the shortest DT (1.77 years) was similar to that of the quartile with the longest DT (1.77 years) (P = 0.760) and multivariate analysis revealed no association between tumour DT and disease-free survival. Conclusion: The rate of growth of colorectal liver metastases prior to surgery should not be used as a prognostic factor when counselling patients prior to resection. Disclosure of interest: None Declared.